2011
DOI: 10.1186/1472-6874-11-10
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary exposed in early motherhood - a qualitative study exploring experiences of mothers with type 1 diabetes

Abstract: BackgroundWomen with type 1 diabetes face several challenges during pregnancy, childbirth and in relation to breastfeeding. It is therefore of utmost importance to consider their need for specific support, early postpartum as well as in daily life after discharge from maternity care. Few studies have investigated these aspects of healthcare. The aim of this study was to explore experiences after childbirth regarding breastfeeding, glycemic control, support and well-being in women with type 1 diabetes.MethodsA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 32 publications
5
53
1
Order By: Relevance
“…Suckling was shown to reduce maternal glucose levels but did not cause hypoglycaemia in most episodes (85%). This is not in line with other studies with self-reports of more frequent hypoglycaemic episodes and fluctuating blood glucose levels (Berg & Sparud-Lundin, 2012; Edwards, Speight, Bridgman, & Skinner, 2016; Sparud-Lundin & Berg, 2011). This can be explained by the fact that Achong et al (2016) and Stage et al (2006) did not measure blood glucose levels in the early postpartum period, for example, before 2 months after childbirth.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Suckling was shown to reduce maternal glucose levels but did not cause hypoglycaemia in most episodes (85%). This is not in line with other studies with self-reports of more frequent hypoglycaemic episodes and fluctuating blood glucose levels (Berg & Sparud-Lundin, 2012; Edwards, Speight, Bridgman, & Skinner, 2016; Sparud-Lundin & Berg, 2011). This can be explained by the fact that Achong et al (2016) and Stage et al (2006) did not measure blood glucose levels in the early postpartum period, for example, before 2 months after childbirth.…”
Section: Discussioncontrasting
confidence: 76%
“…A majority reported considerably more unstable glycaemia, especially during the first two months, and more hypoglycaemic episodes during the breastfeeding episode (Berg & Sparud-Lundin, 2012; Berg, Erlandsson, & Sparud-Lundin, 2012). A qualitative study has revealed that women with T1DM experience a disruption in care delivery after the child is born, although they face a challenging everyday life as new mothers with the additional burden of having diabetes (Sparud-Lundin & Berg, 2011). To develop sufficient health care for these women, there is a need to gain a deeper understanding of how they handle this vulnerable phase with less professional support than needed.…”
Section: Introductionmentioning
confidence: 99%
“…Periods of hypoglycaemia were very prolonged in some subjects, and occurred during periods of breastfeeding; the potential for cognitive impairment and progression to severe hypoglycaemia could put the infant at risk. 9 In the present study, interpreting (and predicting) insulin dosage was difficult with such a small number of participants. Overall, mothers reduced their basal insulin dose to below prepregnancy values by week 4 post-partum, consistent with previous observations.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] Unsurprisingly, qualitative evidence suggests that many women with type 1 diabetes find post-partum selfmanagement to be challenging, to which fear of hypoglycaemia may contribute. 8,9 The aim of the present study was to monitor glycaemic control in women with type 1 diabetes for 4 weeks post-partum, with a particular focus on the frequency of hypoglycaemia.…”
Section: Introductionmentioning
confidence: 99%
“…Some women note a sense of dismissal at the end of the pregnancy [1,2]; once childbirth occurs, the relationship between the obstetric provider and a woman may be abruptly dissolved, with only one return visit after childbirth. The postpartum visit, which typically occurs near the sixth week after delivery, tends to focus more on the reproductive system, with less attention given to general well-being, adjustment to motherhood, and health promotion.…”
Section: Introductionmentioning
confidence: 99%